2023
DOI: 10.3390/cells12131705
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chondroitin Sulfate Proteoglycan 5 in Steroid-Induced Cataract

Abstract: Steroid-induced cataracts (SIC) are defined as cataracts associated with the administration of corticosteroids. Long-term glucocorticoid treatment for inflammatory diseases reportedly increases the risk of SIC, and steroids can induce cataracts by disrupting ocular growth factor balance or homeostasis. In this study, we verified the effect of chondroitin sulfate proteoglycan 5 (CSPG5) using dexamethasone (dexa)-treated human lens epithelial (HLE-B3) cells and the lens epithelium from the anterior capsule of SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 65 For instance, it has been demonstrated that dexamethasone may interfere with pivotal pathways which regulate lens cell homeostasis, migration and differentiation. 67 Moreover, dexamethasone showed to increase the stiffness of trabecular meshwork cells in vitro, by inducing over-expression of contractile proteins and synthesis of extracellular matrix. 68 In addition, the accumulation of steroid molecules in the trabecular meshwork may determine increase in intraocular volume and obstruction due to precipitation which also play a role in IOP elevation.…”
Section: Dex Intravitreal Implant and Anti-vegf Injections For Dmementioning
confidence: 99%
“… 65 For instance, it has been demonstrated that dexamethasone may interfere with pivotal pathways which regulate lens cell homeostasis, migration and differentiation. 67 Moreover, dexamethasone showed to increase the stiffness of trabecular meshwork cells in vitro, by inducing over-expression of contractile proteins and synthesis of extracellular matrix. 68 In addition, the accumulation of steroid molecules in the trabecular meshwork may determine increase in intraocular volume and obstruction due to precipitation which also play a role in IOP elevation.…”
Section: Dex Intravitreal Implant and Anti-vegf Injections For Dmementioning
confidence: 99%